EPISTEMOLOGI BERPAKAIAN KELOMPOK SALAFI BANYUMAS: Studi Living al-Qur’an - Ismail (Jurnal El-Hamra : Kependidikan dan Kemasyarakatan, 2021)
Living Qur'an or Qur'an in every day life is a manifestation of understanding the verses of the Koran that are practiced in everyday life. One form of living Qur'an practice is the wearing of clothes by the Salafi Banyumas group. Clothing that is different from the customs of the surrounding community is a distinctive feature of the Banyumas Salafi group. This usage cannot be separated from the methods and sources of knowledge they use in understanding the verses of the al-Qur'an. This study uses general epistemological theory, as an analytical tool in assessing the sources and understanding of Salafi Banyumas about dress. From this analysis it can be concluded that the source of their understanding of the hadith in their dress is the al-Qur'an, hadith, salaf opinion, language and reason as a source of analogy to the problem. Salafi Banyumas uses a textualnormative approach which is not comprehensive, the reading is not broad enough to make it a textual understanding. In addition, Salafi Banyumas uses deductive thinking and tends to be textual, this understanding is justified by the validity of the truth of coherence, namely the conformity between text and practice and authoritarianism with encouragement from certain parties.Key Words: living Qur'an, Salafi, clothing